ANOTHER PROOF FOR SINGULAR VALUES DECOMPOSITION - OCTA VITANO (NIM: 20107042), FEBRUYANTI
In this paper, we proof the singular value decomposition by constructing a function from a metric space to R and using the property that a continous function on a closed and bounded set in a metric space will have a maximum value.